Tumor Necrosis Impacts Prognosis of Patients Undergoing Resection for T1 Intrahepatic Cholangiocarcinoma - Tsilimigras, DI (2022)
Background: The prognostic impact of tumor necrosis among patients undergoing resection for intrahepatic cholangiocarcinoma (ICC) remains ill-defined. Methods: Patients who underwent curative-intent resection for ICC between 2000 and 2017 were identified using a multi-institutional database. The association of pathologic tumor necrosis with overall survival (OS) and recurrence-free survival (RFS) was examined. Results: Among 757 patients who underwent resection for ICC, tumor necrosis was present in 384 (50.7%) patients (no necrosis: n = 373, 49.3%; <50% necrosis: n = 291, 38.4%; ≥50% necrosis: n = 93, 12.3%). Tumor necrosis was associated with worse OS (5-year OS: no necrosis 39.3% vs. <50% necrosis 34.7% and ≥50% necrosis 24.0%; p = 0.03) and RFS (5-year RFS: no necrosis 25.7% vs. <50% necrosis 13.9% and ≥50% necrosis 18.8%; p < 0.001). After stratifying by T stage, tumor necrosis was able to further stratify prognosis among patients with T1a ICC (5-year RFS: T1a and no necrosis 46.7% vs. T1a and necrosis 36.1%; p = 0.02), and T1b ICC (5-year RFS: T1b and no necrosis 31.1% vs. T1b and necrosis 11.2%; p = 0.006), but was not associated with outcomes among patients with more advanced T2-T3 disease. Patients with T1a ICC and tumor necrosis had similar 5-year RFS as individuals with T1b ICC and no tumor necrosis (36.1% vs. 31.1%; p = 0.66). Conclusion: Tumor necrosis was associated with worse prognosis among patients with T1 ICC. Tumor necrosis for T1 ICC should be considered as an important factor to further stratify outcomes of patients with early T-stage ICC.